REGIONAL DIFFERENTIATION OF THE DEVELOPMENT OF THE EDUCATIONAL - INTELLECTUAL COMPONENT OF UKRAINE’S HUMAN POTENTIAL - Stepura T.M., T.M. (The actual problems of regional economy development, 2021)
The article is dedicated at studying the features of regional differentiation of the development of the educational -intellectual component of human potential in Ukraine. The aim is to develop a methodology for assessing such differentiation for further justification of educational policy. The key and scientifically new in the methodology is to take into account the basic provisions of qualiology, which allows to reflect the qualitative essence of the category of human potential and its component. To do this, the study clarified the essence and component structure of human potential in terms of its quality. The method of its qualimetric estimation is substantiated taking into account the requirements of relativity of estimation, problems of definition of the standard, possibility of inclusion in the analysis of nominal variables that is provided by use of receptions of taxonomic and discriminant analyzes. The latter, in particular, solves the problem of classifying regions according to the semantic indicator of development of educational and intellectual component of human potential (from high to low), allows to identify variables that have the greatest contribution to distinguishing groups of regions. The system of signs and indicators of development of educational and intellectual component of human potential is developed. The personal aspect of the development of the educational - intellectual component of human potential is explained in the formed knowledge and abilities of people, and the activity – in the acquisition of education and characterizes its quality, continuity, efficiency of investing in it. The results of the analytical study testified to the existence of regional centers for attracting the educational - intellectual potential of Ukraine, as well as the regions where it is being reduced. The reasons for such differentiation are revealed, which are recommended to be taken into account when forming regional policies of human potential development: first of all, educational, but also migration, employment policy.